SHAPING OF COMPLEX FORMATIONS IN THE RUSSIAN LEGISLATIVE SYSTEM AS A FACTOR OF INTERSECTORAL CODIFICATION - M. F. Matyunin (Russian Journal of Economics and Law, 2011)
The article is devoted to the factors of complex formations shaping in the Russian legislative system during complex codification. In particular, the system of law, as well as other social factors, is viewed as a factor of complex formations shaping.